Global Jane Austen
IX, 296 p. 5 illus.
Keywords: Despite dying in relative obscurity, Jane Austen has become a global force as different readers across time, space and media have responded to her work. This volume examines the ways in which her novels affect individual psychologies and how Janeites experience her work, from visiting her home to public re-enactments to films based on her writings.